Research on the delamination wear properties of the pure carbon strip at the high-sliding speed with electric current. Issue 1 (8th January 2018) - Yang, Hongjuan; Fu, Lin; Liu, Yanhua; Qian, Weiji; Hu, Bo
Abstract : Purpose: This paper aims to investigate the delamination wear properties of a carbon strip in a carbon strip rubbing against a copper wire at the high-sliding speed (380 km/h) with or without electrical current. Design/methodology/approach: The friction and wear properties of a carbon strip in a carbon strip rubbing against a copper wire are tested on the high-speed wear tester whose speed can reach up to 400 km/h. The test data have been collected by the high-speed data collector. The worn surfaces of the carbon strip are observed by the scanning electron microscope. Findings: It was found that there was a significant increase of the delamination wear with the decrease of the normal load when the electric current is applied. The size of the flake-like peeling also increases with the decrease of normal load. The delamination wear extends gradually from the edge of the erosion pits to the surrounding area with the decrease of the normal load. However, the delamination wear never appears in the absence of electric current. It is proposed that the decreased normal load and the big electrical current are the major causes of the delamination wear of the carbon strip. Originality value: The experimental test at high-sliding speed of 380 km/h was performed for the first time, and the major cause of the delamination was discovered in this paper.